Treatment of myocardial interstitial fibrosis in pathological myocardial hypertrophy - Zhu, Fuyu; Li, Peng; Sheng, Yanhui (Frontiers in Pharmacology, 2022)
Pathological myocardial hypertrophy can be caused by a variety of diseases, mainly accompanied by myocardial interstitial fibrosis (MIF), which is a diffuse and patchy process, appearing as a combination of interstitial micro-scars and perivascular collagen fiber deposition. Different stimuli may trigger MIF without cell death by activating a variety of fibrotic signaling pathways in mesenchymal cells. This manuscript summarizes the current knowledge about the mechanism and harmful outcomes of MIF in pathological myocardial hypertrophy, discusses the circulating and imaging biomarkers that can be used to identify this lesion, and reviews the currently available and potential future treatments that allow the individualized management of patients with pathological myocardial hypertrophy.